(3JQGLe Hfi GdhRjQs - (3EHQGgje Hf jMji Hf YHO Gddg Hf GdgGOjs
(3ChdgG (B:s
(3GdMeO ddg GdPi GSHZ YdjfG fYeg Ke HYO Gddg hdg GdMeO deG Thafi HTQa Pdc GdGfJSGH s
(3BNQgG (B:s
(3cGfJ haGI SjOi CejQ GdeDefjf TgGH GdOjf bOS Gddg QhMg HbOQ QHY Gddjd ef GddjdI GdeSaQ Yf jhe GdGMO SGHY TgQ LeGOi GdGNQI ef SfI NeS hSJjf hJSYeGFI s
(3aQZ ef LeYgG SfI (B965(3g`s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3eJaQbGJs